Incidental Cutaneous Reaction Patterns: Epidermolytic Hyperkeratosis, Acantholytic Dyskeratosis, and Hailey-Hailey-Like Acantholysis: A Potential Marker of Premalignant Skin Change - Erich M. Gaertner (Journal of Skin Cancer)
Focal acantholytic dyskeratosis (FAD), epidermolytic hyperkeratosis (EHK), and Hailey-Hailey-like acantholysis (HH) represent unique histology reaction patterns, which can be associated with defined phenotypic and genotypic alterations. Incidental microscopic foci demonstrating these patterns have been identified in skin and mucosal specimens in association with a gamut of disease processes. These changes, when secondary, are of unclear etiology and significance. The following study further analyzes the incidence and association of these histologic patterns in a routine pathology/dermatopathology practice.